Why did high-dose rosuvastatin not improve cardiac remodeling in chronic heart failure? Mechanistic insights from the UNIVERSE study - Ashton, E.; Windebank, E.; Skiba, M.; Reid, Christopher; Schneider, H.; Rosenfeldt, F.; Tonkin, A.; Krum, H. (2011)
Background: Statins are often prescribed for prevention of atherosclerotic outcomes in patients who have chronic heart failure (CHF), if this has an ischaemic etiology. These agents may also possess additional properties, independent of effects on blood lipid levels, which may have an effect on cardiac remodeling. However, beneficial effects were not observed in the recent UNIVERSE trial. Methods: We prospectively planned a sub-study of UNIVERSE to explore relevant mechanistic effects of rosuvastatin, including effects on collagen turnover and plasma coenzyme Q10 (CoQ) levels. Additionally, CoQ levels in CHF patients receiving chronic statin therapy were measured. Results: CoQ levels were significantly reduced after 26 weeks of rosuvastatin statin therapy (n = 32), compared to placebo (n = 37) in CHF patients in UNIVERSE trial. Patients with CHF (n = 56) matched for age, gender and severity of disease who had been taking statins for 12 months or longer had CoQ levels of 847 ± 344 nmol/L, significantly lower than 1065.4 ± 394 nmol/L in UNIVERSE patients at baseline (p = 0.0001). Serum types I and III N-terminal procollagen peptide (PINP and PIIINP), measures of collagen turnover which can contribute to cardiac fibrosis were significantly increased in the rosuvastatin group compared to baseline in UNIVERSE patients (PINP: p = 0.03, PIIINP: p = 0.001). Conclusion: In conclusion putative beneficial effects of statin therapy on cardiac remodeling in UNIVERSE may have been negated by increases in collagen turnover markers as well as a reduction in plasma CoQ levels in these patients with CHF. © 2010 Elsevier Ireland Ltd. All rights reserved.